The effect of cigarette smoke extract on the activity of clarithromycin with anti-pseudomonal agents on growth and biofilm formation of Pseudomonas aeruginosa - Cholo, Moloko C. (University of Pretoria, 2023)
Dissertation (MSc (Medical Immunology))--University of Pretoria, 2023.